HOUSEHOLDS IN THE ROMANIAN RURAL AREA - THEORETICAL MODEL - Lorena CHIȚEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romanian rural area is stimulated by the activities of rural households as the main demographic, social, economic and cultural resources holder. The households are able to dispose of these resources as they see, based on the the conditions generated by social-economic-cultural environment of the community to which they belong. For an overview of the socio-economic development level at national and regional level, composite indicators are useful, without omitting, thou, individual indicators. This territorial profile analysis can highlight the particularities of each area.